Freud and Philosophy of Mind, Volume 1 Reconstructing the Argument for Unconscious Mental States - Wakefield, Jerome C. (Springer International Publishing, 2018)
This book consists of a focused and systematic analysis of Freud's implicit argument for unconscious mental states. The author employs the unique approach of applying contemporary philosophical methods, especially Kripke-Putnam essentialism, in analyzing Freud's argument. The book elaborates how Freud transformed the intentionality theory of his Cartesian teacher Franz Brentano into what is essentially a sophisticated modern view of the mind. Indeed, Freud redirected Brentano's analysis of consciousness as intentionality into a view of consciousness-independent intentionalism about the mental that in effect set the agenda for latter-twentieth-century philosophy of mind. .